Factors associated with vaccination coverage in children < 5 years in Angola - Manuel Falcão Saturnino de Oliveira; Edson Zangiacomi Martinez; Juan Stuardo Yazlle Rocha (Universidade de São Paulo, 2014)
OBJECTIVE To analyze vaccination coverage and factors associated with a complete immunization scheme in children < 5 years old. METHODS This cross-sectional household census survey evaluated 1,209 children < 5 years old living in Bom Jesus, Angola, in 2010. Data were obtained from interviews, questionnaires, child immunization histories, and maternal health histories. The statistical analysis used generalized linear models, in which the dependent variable followed a binary distribution (vaccinated, unvaccinated) and the association function was logarithmic and had the children's individual, familial, and socioeconomic factors as independent variables. RESULTS Vaccination coverage was 37.0%, higher in children < 1 year (55.0%) and heterogeneous across neighborhoods; 52.0% of children of both sexes had no immunization records. The prevalence rate of vaccination significantly varied according to child age, mother's level of education, family size, ownership of household appliances, and destination of domestic waste. CONCLUSIONS Vulnerable groups with vaccination coverage below recommended levels continue to be present. Some factors indicate inequalities that represent barriers to full immunization, indicating the need to implement more equitable policies. The knowledge of these factors contributes to planning immunization promotion measures that focus on the most vulnerable groups.